Technological choice under organizational diseconomies of scale - Anja Schöttner; Bruno Deffains (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
With adverse selection, diseconomies of scale associated with hierarchies may induce the implementation of a second-best technology. This occurs whenever rents to lower tiers of the hierarchy increase faster than total surplus. This is more likely with longer hierarchies.
Keywords: D82; L23; O33; 330; Adverse Selection; Hierarchies; Technology